Qatar - Scott-Jackson, Julie (Archaeopress Publishing, 2022)
"Qatar: Evidence of the Palaeolithic Earliest People Revealed, with full text in both English and Arabic, tells the story of the long and difficult search to discover the identity of the first people to inhabit the sovereign State of Qatar, which is situated on a peninsula, that extends into the Arabian Gulf. The book synthesises the results of extensive fieldwork by the PADMAC Unit with the many diverse historical records and reports of investigations, beginning with Holgar Kapel’s, in the early 1950s. The archaeology of the State of Qatar is an important part of the cultural heritage of the world. The loss of archaeological sites to urban and industrial development since the 1950s has been inevitable but the loss of over 30 years of Palaeolithic research in Qatar, an area of prehistoric significance, as a result of academic dissension, is certainly regrettable. The work of the PADMAC Unit in Qatar now marks the end of this Palaeolithic research hiatus."